2018
DOI: 10.1016/j.drugalcdep.2018.05.034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quinine in two bottle choice procedures in C57BL6 mice: Opioid preference, somatic withdrawal, and pharmacokinetic outcomes

Abstract: Previous reports assessing morphine effects in two bottle choice (TBC) paradigms often use taste adulterants such as sweeteners (e.g., saccharin) and/or bitterants (e.g., quinine) to demonstrate morphine preference with C57BL6 mice. The effect of these additional components on the morphine preference of C57BL6 remains poorly understood. Thus, we sought to elucidate the interrelationship of morphine and quinine in the TBC paradigm. As expected, when morphine was included in the opposite bottle from quinine, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Human studies of ethanol drinking initiation distinguish between the experiences of the first drink and the first intoxicationwhich often do not coincideon their effect on drinking habits in adulthood (Samson, 1987). We speculate that consumptive ethanol preference in Drosophila similarly depends on suprathreshold substance intake, as shown in studies of self-administered oral preference for drugs of abuse in rodents (Grim et al, 2018). This explanation is consistent with previous reports that ethanol preference increases with the duration and intensity of exposure (Devineni and Heberlein, 2009; Peru Y. Colón de Portugal et al, EtOH, ethanol; PI, preference index; S, sucrose; T, tryptone.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Human studies of ethanol drinking initiation distinguish between the experiences of the first drink and the first intoxicationwhich often do not coincideon their effect on drinking habits in adulthood (Samson, 1987). We speculate that consumptive ethanol preference in Drosophila similarly depends on suprathreshold substance intake, as shown in studies of self-administered oral preference for drugs of abuse in rodents (Grim et al, 2018). This explanation is consistent with previous reports that ethanol preference increases with the duration and intensity of exposure (Devineni and Heberlein, 2009; Peru Y. Colón de Portugal et al, EtOH, ethanol; PI, preference index; S, sucrose; T, tryptone.…”
Section: Resultssupporting
confidence: 91%
“…Human studies of ethanol drinking initiation distinguish between the experiences of the first drink and the first intoxication-which often do not coincide-on their effect on drinking habits in adulthood (Samson, 1987). We speculate that consumptive ethanol preference in Drosophila similarly depends on suprathreshold substance intake, as shown in studies of self-administered oral preference for drugs of abuse in rodents (Grim et al, 2018). This explanation is consistent with previous reports that ethanol preference increases with duration and intensity of exposure Heberlein, 2009, Peru Y. Colón de Portugal et al, 2014) and that ethanol preference is attenuated or abolished when the CAFE vials are supplemented with additional food source (Park et al, 2018)-which would effectively decrease overall consumption of the test diets and thus the mixed-in ethanol, making it less likely for animals to ingest enough ethanol to meet the threshold for establishing preference.…”
Section: Table 1 Summary Of Feeding Parameters On Various Mediamentioning
confidence: 65%
“…On the other hand, when quinine is included in the alternative bottle, a preference for the morphine solution is observed, suggesting that quinine is effective in driving morphine consumption and generating dependence. However, several reports demonstrated that, in this paradigm, high morphine preference is not related to the rewarding properties of the drug, but its preference is influenced by the degree of quinine aversion [ 15 , 16 ]. Thus, it was postulated that the aversion to the bitter taste of quinine is what leads to the maintenance of relatively high levels of fluid consumption from the morphine bottle [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we used a two-bottle choice method for administering morphine. Our method used a 0.2% saccharin solution in both the morphine and vehicle bottles, which generally produces a morphine preference in C57Bl6/J mice ( Belknap et al, 1993 ), and avoids the confound of quinine influencing choice consumption more than morphine ( Grim et al, 2018 ). We used an established model of CSS ( Zhu et al, 2018 ) with non-invasive sleep (behavioral quiescence) recording and automated drinking sensors to assess the effect of prolonged sleep disturbance on both voluntary consumption and associative rewarding properties of morphine in male mice.…”
Section: Introductionmentioning
confidence: 99%